Health Education For Adolescents On The Prevention Of Sexually Transmitted Diseases (STDs) - Hairudin La Patilaiya (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
Sexually transmitted diseases or STDs for short are diseases caused by unhealthy sexual relations. STDs are usually experienced by teenagers, adults, and the elderly due to deviant behavior such as free sex, anal sex, oral sex, or because of direct contact with sufferers through the genital tract, skin touch, vaginal fluids, sperm fluid and sexual intercourse that is not use condoms and other sexual safety devices. Factors that influence adolescent behavior are personal experience, the influence of others, cultural influences, mass media, educational institutions, religion and emotional factors. Therefore, it is necessary to conduct education and socialization on the prevention of sexually transmitted diseases using lecture methods, question and answer and discussion as well as aids or poster media used. From the results of the education and socialization activities, it is hoped that it can prevent sexually transmitted diseases and increase the generation of healthy living in adolescents at GMIH Eben Haezer Church, Ternate.